Gambaran Tingkat Kecemasan Mahasiswa Tingkat Akhir Program Studi Pendidikan Profesi Ners - Amalia, Wini; Abdilah, Hadi; Tarwati, Kartika (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Anxiety is a state that can result in a person feeling uncomfortable, agitated, afraid, worried, and not at ease followed by various physical symptoms Anxiety is also a person's subjective feelings about tension, fear, nervousness, and worry related to the arousal of the nervous system. The high level of anxiety causes a person's normal life to be difficult such as disruption of activities and social life. anxiety is one of the many types of emotional and behavioral disorders. The purpose of this study is to find out the Overview of the Anxiety Level of Final Year Students of the Ners Professional Education Study Program. This research method uses Descriptive Quantitative Analysis with a cross sectional approach. The final year student population of the Ners Professional Education Study Program at Muhammadiyah Sukabumi University is 49 people. The results showed that the majority of respondents experienced anxiety (46.9%), a small percentage of respondents experienced panic by (4.1%).vIt can be concluded that the sex of the respondents was (71.4%) female and (28.6%) male. the majority of respondents were aged 20-25 (78%), and no respondents were aged 26-30 (0%). So the majority of respondents experienced no anxiety (46.9%), and a small proportion of respondents experienced panic (4.1%). Suggestions for future researchers This research is expected to be a reference for further research with experimental research regarding actions that can be given to reduce students' anxiety levels in dealing with final assignments both at undergraduate level and Nurses Education. Keywords: Anxiety, Final Year Students  ABSTRAK Kecemasan merupakan keadaan yang dapat mengakibatkan seseorang merasa tidak nyaman, gelisah, takut, khawatir, dan tidak tentram diikuti berbagai gejala fisik kecemasan juga yaitu perasaan subjektif seseorang tentang ketegangan, ketakutan, gugup, dan khawatir berhubungan dengan gairah dari sistem saraf. Tingginya tingkat kecemasan menyebabkan kehidupan normal seseorang menjadi sulit seperti terganggunya kegiatan dan kehidupan sosial. Kecemasan merupakan salah satu dari berbagai jenis gangguan emosi dan perilaku. Tujuan penelitian ini untuk mengetahui Gambaran Tingkat Kecemasan Mahasiswa Tingkat Akhir Program Studi Pendidikan Profesi Ners. Metode penelitian ini menggunakan Kuantitatif Deskriptif Analitik dengan pendekatan cross-sectional. Populasi mahasiswa tingkat akhir Program Studi Pendidikan Profesi Ners di Universitas Muhammadiyah Sukabumi sebanyak 49 orang. Hasil penelitian menunjukan bahwa mayoritas responden mengalami ketidak cemasan sebesar (46,9%), sebagian kecil responden mengalami panik sebesar (4,1%). Dapat disimpulkan Jenis kelamin responden yaitu (71,4%) perempuan dan (28,6%) laki-laki. mayoritas responden berada pada usia 20-25 yaitu (78%), dan tidak ada responden berada pada usia 26-30 yaitu (0%). Jadi mayoritas responden mengalami tidak cemas yaitu (46,9%), dan sebagian kecil responden mengalami panik yaitu (4,1%). Saran bagi peneliti selanjutnya Penelitian ini diharapkan menjadi referensi untuk penelitian selanjutnya dengan penelitian eksperimental mengenai tindakan yang dapat diberikan untuk menurunkan tingkat kecemasan mahasiswa dalam menghadapi tugas akhir baik di tingkat S1 maupun Pendidikan Ners. Kata Kunci: Kecemasan, Mahasiswa Tingkat Akhir.